Umngqungqo, yincwadi (Just those two words) (International Library of African Music, 2015)
This is a very short recording of just the two words umngqungqo and incwadi, each said several times. The words are umngqungqo, the dance from girls' initiation, and incwadi, a letter. The recordings began with a song from umngqungqo and incwadi was the final word of the words on Track 7. One is tempted to let one's imagination go to work: Joseph Ntwanambi, the hungry prisoner far from home, may have been thinking of a girl whom he had hoped to marry. She would be available for marriage after her initiation. He had found work, and now he had the oxen he needed for the bride price. How he must have longed to write to her or to his family about this! Or perhaps he was remembering things that had happened a long time ago. This of course is pure speculation. But his recordings clearly show a deep sense of nostalgia.
Keywords: African Music